Phosphate fluorescent glass ceramic capable of emitting light in pure white light and preparation method of phosphate fluorescent glass ceramic
By doping Dy3+, Tm3+ and Eu3+ ions in phosphate fluorescent glass ceramic materials and preparing materials rich in BaZn2(PO4)2 nanocrystals, the shortcomings of existing white LEDs in color temperature and chromaticity coordinate adjustment are solved, and efficient and stable near-positive white light emission is achieved.
Patent Information
- Application Number
- CN202311261094.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
The existing manufacturing methods of white LEDs are limited in the adjustment of color temperature and chromaticity coordinates, and cannot obtain ideal color rendering performance. There are problems such as inconsistent use temperature and life of phosphors, which affects the luminescence quality.
P2O5-BaO-ZnO-B2O3 glass matrix, doped with Dy3+, Tm3+ and Eu3+ ions, was used to prepare phosphate fluorescent glass ceramic materials rich in BaZn2(PO4)2 nanocrystals by melt quenching.
It realizes the purity and luminous stability of the luminous color, has good thermal stability and efficient photoelectric conversion efficiency, the chromaticity coordinates are close to positive white light emission, and the color temperature is close to 5802K.
Smart Images

Figure CN119707293A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phosphate fluorescent glass ceramics, and in particular to a phosphate fluorescent glass ceramic emitting positive white light and a preparation method thereof. Background Art
[0002] Currently, in the field of lighting, phosphor-converted white light emitting diodes (pc-WLEDs) have gradually replaced traditional lighting equipment and become a hot topic in white light LED research due to their high energy efficiency, high environmental friendliness, high visible light emission efficiency, good thermal stability, and long service life. The current manufacturing of pc-wLEDs is mainly based on the method of combining phosphors and chips. The first of the most commonly used methods is to combine the blue InGaN chip with the yellow YAG:Ce 3+ The advantage of this method is that it directly combines blue light excitation and yellow light to finally emit white light. Since this method has high luminous efficiency and low production cost, it is widely used in the market. However, this method is relatively limited in the adjustment of color temperature and chromaticity coordinates, and cannot obtain ideal color rendering performance. Another popular method is to achieve white light emission by combining ultraviolet or near-ultraviolet LED chips with three types of blue, green and red phosphors. This method can produce white light with a higher color temperature and greatly improves color reproduction. The current color rendering index (CRI) value can reach more than 80. However, this method faces the problem of inconsistent use temperature and service life of the three encapsulated phosphors, which affects the luminous quality of pc-wLED. In addition, there is the problem of reabsorption of the three primary color phosphors, that is, green and red light will absorb blue light, thereby reducing the luminous efficiency. Therefore, researchers began to seek to use ultraviolet or near-ultraviolet LED chips to excite single-component white light phosphors to solve these problems. This method is different from the previous multi-component phosphors, and can more efficiently convert selectively excited light, with higher photoelectric conversion efficiency and spectral compatibility. In addition, single-component white light phosphors also have high stability, low light decay and excellent color rendering properties. Studies have shown that phosphoborate glass with a formula of P2O5-BaO-ZnO-B2O3 has good optical properties, low dispersion, low phonon energy, and good transparency in the ultraviolet to near-infrared region. It is a good matrix material for rare earth ion-doped fluorescent glass ceramics. With the continuous maturity of single-component white light phosphors in manufacturing technology, it has become one of the current research hotspots of white light LEDs. Summary of the invention
[0003] The technical problem to be solved by the present invention is to provide a fluorescent glass ceramic having good stability and tunable white light emission after adjustment, in view of the shortcomings of the prior art. A phosphate fluorescent glass ceramic that can emit near-positive white light and a preparation method thereof, the glass ceramic material has good thermal stability, realizes pure luminescent color and stable luminescence, and the preparation method of the glass ceramic material is simple and efficient.
[0004] The technical solution adopted by the present invention to solve the above technical problems is: a phosphate fluorescent glass ceramic material emitting positive white light, the mass percentage composition of the phosphate fluorescent glass ceramic material is: P2O5 28-38%, BaO6-12%, ZnO 36-48%, B2O3 14-18%, the glass matrix is doped with Dy 3+ 、Tm 3+ and Eu 3+ , doped in the form of compounds, wherein the doped dysprosium-containing compounds, thulium-containing compounds and europium-containing compounds account for 0.25%-1%, 0.25%-1% and x of the total mass of other raw materials respectively, 0.25%≤x≤1.0%.
[0005] The dysprosium-containing compound is Dy2O3, the thulium-containing compound is Tm2O3, and the europium-containing compound is Eu2O3.
[0006] The chromaticity coordinates of the phosphate fluorescent glass ceramic are (0.2951-0.5856, 0.3092-0.4136).
[0007] The raw materials BaCO3, ZnO, NH4H2PO4, H3BO3, Dy2O3, Tm2O3 and Eu2O3 are mixed and ground, calcined, melt quenched, ground, pressed and molded, and then fired to the glass softening point and cooled to obtain the glass matrix doped with Dy 3+ , Tm 3+ ,Eu 3+ It is doped in the form of compounds, wherein the doped dysprosium compound Dy2O3, thulium compound Tm2O3 and europium compound Eu2O3 account for 0.25%-1%, 0.25%-1% and 0.25-1% of the total mass of other raw materials respectively, and BaZn2(PO4)2 nanocrystals are precipitated in the glass matrix.
[0008] The glass ceramic material of the present invention adopts a P2O5-BaO-ZnO-B2O3 glass matrix, wherein P2O5 provides a rigid structure, so that the glass ceramic material has the advantages of high hardness and good mechanical properties, and at the same time creates nucleation and boundary conditions for the glass crystallization process; the role of introducing ZnO and BaO is to provide necessary constituent elements for the precipitation of nanocrystalline BaZn2(PO4)2, and the role of B2O3 is to lower the melting point of the mixture, making heating more convenient.
[0009] The matrix glass of the glass ceramic material of the present invention has good forming ability and thermal stability, and also has low phonon energy and good transparency. It is a good matrix for rare earth ions, has low molding temperature, and low raw material cost. Its luminous properties: chromaticity coordinates are (0.2951-0.5856, 0.3092-0.4136), and further preferred color coordinates are (0.3264, 0.3240), close to positive white light (0.33, 0.33), color-related temperature is 5802K, close to positive white light emission, and doped Dy 3+ 、Tm 3+ 、Eu 3+ By doping into nanocrystalline BaZn2(PO4)2 without destroying the structure of the crystal, a large number of rare earth luminescent ions are embedded in a low phonon energy environment, which is beneficial to reduce the probability of non-radiative transitions and improve the luminescence efficiency.
[0010] The present invention provides a method for preparing a phosphate fluorescent glass ceramic that emits positive white light, comprising the following steps:
[0011] 1) Raw material preparation: weigh the raw materials and mix them evenly to obtain a mixed powder;
[0012] 2) Melting and quenching: The powder obtained in step 1) is calcined, and after melting, the melt is quenched to obtain a precursor glass, and the precursor glass is ground to obtain a glass powder;
[0013] 3) Tableting: pouring the glass powder obtained in step 2) into a mold and pressing it into a round green tablet;
[0014] 4) Heat treatment: The green disc obtained in step 3) is heat treated and cooled to room temperature to obtain rare earth Dy 3+ / Tm 3+ / Eu 3+ Co-doped BaZn2(PO4)2 fluorescent glass-ceramics.
[0015] Preferably, in step 2), the calcination temperature is 1300-1350° C. and the calcination time is 2-4 hours;
[0016] The melt was poured into deionized water for quenching.
[0017] Preferably, in step 3), a hydraulic press is used for pressing, and the hydraulic press uses a pressure of 20-40 MPa and a holding time of 60-90 seconds.
[0018] Preferably, in step 4), the heat treatment temperature is 600° C.-650° C., and the heat treatment time is 2-4 hours.
[0019] As a preferred method, the rare earth Dy is obtained in step 4) 3+ / Tm 3+ / Eu 3+ The chromaticity coordinates of the co-doped BaZn2(PO4)2 fluorescent glass-ceramic material are (0.2951-0.5856, 0.3092-0.4136).
[0020] Specifically, the present invention provides a rare earth Dy 3+ / Tm 3+ / Eu 3+ The preparation method of co-doped BaZn2(PO4)2 glass-ceramic material is carried out according to the following steps:
[0021] 1) Raw material preparation: BaCO3, ZnO, NH4H2PO4, H3BO3, Dy2O3, Tm2O3 and Eu2O3 are used as raw materials, according to the mass percentage: P2O5 28-38%, BaO 6-12%, ZnO 36-48%, B2O3 14-18%, wherein the doped dysprosium compound, thulium compound and europium compound account for 0.25%-1%, 0.25%-1% and x, 0.25≤x≤1.0 of the total mass of other raw materials, respectively, weigh the raw materials, grind them in an agate mortar for 2-4h, mix them thoroughly and evenly, and obtain a mixture powder;
[0022] 2) Melting and quenching: The powder obtained in step 1) is placed in a muffle furnace at a temperature of 1300-1350° C. and calcined for 2-4 hours. After melting, the melt in the high-purity corundum crucible is poured into deionized water for quenching to obtain a precursor glass, and then the precursor glass is ground for 2-4 hours to obtain a glass powder;
[0023] 3) tabletting: weigh about 0.15-0.2 g of the powder obtained in step 2) and pour it into a mold with a diameter of 10-20 mm, and press it into a round tablet by a hydraulic press at a pressure of 20-40 MPa for 60-90 seconds;
[0024] 4) Heat treatment: The green disc obtained in step 3) is placed in a muffle furnace for heat treatment at a temperature of 600°C-650°C for 2-4 hours, and then cooled naturally to room temperature to obtain rare earth Dy 3+ / Tm 3+ / Eu 3+ Co-doped BaZn2(PO4)2 fluorescent glass-ceramic materials.
[0025] The glass ceramic material of the present application has high crystallinity and transparency, and its excitation spectrum is in the ultraviolet region. After adjustment, a suitable Eu 3+ The doping amount can realize the emission of near-pure white light. The sample of the present invention has good thermal stability and excellent luminescence performance, and can be used as a new type of fluorescent material in the field of luminescence.
[0026] Compared with the prior art, the advantages of the present invention are:
[0027] 1. The glass ceramic material obtained by the present invention is rich in a large number of BaZn2(PO4)2 nanocrystals by a melt quenching method and then partially crystallized by heat treatment. The borophosphate matrix glass has good forming ability and thermal stability, low phonon energy and good transparency, and is a good matrix for rare earth ions. It has low molding temperature and low raw material cost. 3+ 、Tm 3+ 、Eu 3+ It can be embedded in a low phonon energy environment, which is beneficial to increase its luminescence intensity, reduce the probability of non-radiative transitions, and improve luminescence efficiency.
[0028] 2. With Dy 3+ and Eu 3+ Compared with double doping, the fluorescent glass ceramics of the present invention are 3+ 、Tm 3+ 、Eu 3+ doping, three doping exists from Tm 3+ To Eu 3+ And from Dy 3+ To Eu 3+ The energy transfer of Dy and Eu is realized, and the color temperature drops from 7887K to 5802K, with a change of about 400K per level. Compared with Dy and Eu double doping, the change is more stable, the light color is more coordinable and controllable. The color coordinate difference with the standard positive white light (0.33, 0.33) is smaller. At the same temperature, the thermal stability is two percentage points higher on average, and the activation energy is about 1.2 times. Near-positive white light luminescence is achieved, the chromaticity coordinates are close to positive white light luminescence, and it has good thermal stability and luminescence stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] FIG. 1( a ) is an XRD pattern of the fluorescent glass ceramics in Examples 1, 2, 3, and 4 of the present invention.
[0030] FIG1( b ) is a model of BaZn2(PO4)2 nanocrystals generated in fluorescent glass ceramics in Examples 1, 2, 3, and 4 of the present invention;
[0031] FIG. 2( a ) is a surface SEM image of the fluorescent glass-ceramic in Example 4 of the present invention;
[0032] FIG. 2 ( b - 1 ) is an EDS element mapping image of all elements of the fluorescent glass ceramic in Example 4 of the present invention;
[0033] FIG. 2 ( b - 2 ) is an EDS element mapping image of the Ba element of the fluorescent glass ceramic in Example 4 of the present invention;
[0034] FIG. 2 ( b - 3 ) is an EDS element mapping image of the Zn element of the fluorescent glass ceramic in Example 4 of the present invention;
[0035] FIG. 2 ( b - 4 ) is an EDS element mapping image of the O element of the fluorescent glass ceramic in Example 4 of the present invention;
[0036] FIG2( b - 5 ) is an EDS element mapping image of the P element of the fluorescent glass ceramic in Example 4 of the present invention;
[0037] FIG. 2 ( b - 6 ) is an EDS element mapping image of the Dy element of the fluorescent glass ceramic in Example 4 of the present invention;
[0038] FIG. 2 ( b - 7 ) is an EDS element mapping image of the Tm element of the fluorescent glass ceramic in Example 4 of the present invention;
[0039] FIG2( b - 8 ) is an EDS element mapping image of the Eu element of the fluorescent glass ceramic in Example 4 of the present invention;
[0040] FIG2( c ) is a TEM image of the fluorescent glass-ceramic in Example 4 of the present invention (showing the formation and size of crystals;
[0041] FIG2( d ) is a TEM image of the fluorescent glass-ceramic in Example 4 of the present invention (showing the presence and spacing of lattice fringes);
[0042] FIG3( a ) is an excitation spectrum diagram of the glass ceramics of Examples 1, 2, 3, and 4 of the present invention;
[0043] FIG3( b ) is an emission spectrum diagram of the glass ceramics of Examples 1, 2, 3, and 4 of the present invention;
[0044] Figure 4 For single Dy doping 3+ Ion, Tm 3+ Ions and Eu 3+ Excitation and emission spectra of ion samples;
[0045] FIG5( a) is an emission spectrum of the glass ceramics in Examples 1, 2, 3, and 4 of the present invention;
[0046] FIG5( b ) is a graph showing the intensity variation of the emission spectrum of the glass ceramics in Examples 1, 2, 3, and 4 of the present invention;
[0047] FIG6( a ) is a fluorescence attenuation diagram of the glass ceramics in Examples 1, 2, 3, and 4 of the present invention at 455 nm under excitation at a wavelength of 362 nm;
[0048] FIG6( b ) is a fluorescence attenuation diagram of the glass ceramics in Examples 1, 2, 3, and 4 of the present invention at 575 nm under excitation at a wavelength of 362 nm;
[0049] Figure 7 Dy is the Dy of the fluorescent glass ceramics in Examples 1, 2, 3 and 4 of the present invention. 3+ / Tm 3+ / Eu 3+ Energy level diagram of ;
[0050] Figure 8 is the CIE chromaticity diagram of the fluorescent glass-ceramics in Examples 1, 2, 3, and 4 of the present invention;
[0051] FIG9( a ) is a temperature-dependent emission spectrum of the fluorescent glass-ceramic in Example 4 of the present invention (the inset is the normalized emission spectrum intensity of the sample at 298K-473K);
[0052] FIG. 9( b ) is a graph showing the fluorescent glass ceramic ln[(I0 / I t )-1] and 1 / kT. DETAILED DESCRIPTION
[0053] The technical solution of the present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0054] Embodiment 1:
[0055] (1) BaCO3, ZnO, NH4H2PO4, H3BO3, Dy2O3, Tm2O3 and Eu2O3 were weighed according to the raw material ratio, and the raw materials were weighed according to the mass percentage: P2O5 38%, BaO 12%, ZnO 36%, B2O3 14%, Dy2O3 1%, Tm2O3 0.5%, Eu2O3 0.25%, and ground in an agate mortar for 2 hours to obtain a uniformly mixed powder, which was then transferred to a high-purity corundum crucible;
[0056] (2) placing the powder obtained in step (1) in a muffle furnace at a temperature of 1350° C. and calcining for 2 hours, and after melting, quickly pouring the melt in the high-purity corundum crucible into deionized water for quenching to obtain a precursor glass, and then transferring it to an oven for drying to obtain a solid glass;
[0057] (3) grinding the solid glass obtained in step (2) in an agate mortar for 2 hours to obtain glass powder;
[0058] (4) Weigh 0.2 g of the powder obtained in step (3) and pour it into a mold with a diameter of 20 mm. Press it into a green round tablet using a hydraulic press with a holding pressure of 40 MPa for 60 seconds.
[0059] (5) The green disc obtained in step (4) is placed in a muffle furnace for heat treatment at 650° C. for 2 hours, and then cooled naturally to room temperature to obtain rare earth Dy 3+ / Tm 3+ / Eu 3+ Co-doped BaZn2(PO4)2 fluorescent glass-ceramic materials.
[0060] The XRD of the BaZn2(PO4)2 glass ceramic obtained in step (5) is shown in Figure 1. Both the crystalline peak and the amorphous peak exist, and the peak position and intensity of the crystalline peak correspond to the PDF card of BaZn2(PO4)2, indicating the existence of the corresponding crystalline phase. Under the excitation of 362nm light source, the measured emission spectrum is shown in Figure 5, showing that Dy 3+ / Tm 3+ / Eu 3+ The characteristic emission peak position of co-doped BaZn2(PO4)2 phosphate glass ceramics. The color coordinates are (0.3045, 0.3169), see Figure 8 The position indicated by "b" has a color temperature of 7110K, which is cold white light emission. The XRD spectrum of the fluorescent glass ceramic is shown in Figure 1(a), the model of the BaZn2(PO4)2 nanocrystal generated in the fluorescent glass ceramic is shown in Figure 1(b), the excitation spectrum of the glass ceramic is shown in Figure 3(a), the emission spectrum of the glass ceramic is shown in Figure 3(b), the emission spectrum of the glass ceramic is shown in Figure 5(a), the emission spectrum intensity change of the glass ceramic is shown in Figure 5(b), the fluorescence attenuation of the glass ceramic at 455nm under 362nm wavelength excitation is shown in Figure 6(a), the fluorescence attenuation of the glass ceramic at 575nm under 362nm wavelength excitation is shown in Figure 6(b), the Dy 3+ / Tm 3+ / Eu 3+ The energy level diagram is as follows Figure 7 As shown in the CIE chromaticity diagram of medium fluorescent glass ceramics Figure 8 shown.
[0061] Embodiment 2:
[0062] (1) BaCO3, ZnO, NH4H2PO4, H3BO3, Dy2O3, Tm2O3 and Eu2O3 were weighed according to the raw material ratio, and the raw materials were weighed according to the mass percentage: P2O5 35%, BaO 10%, ZnO 40%, B2O3 15%, Dy2O3 0.75%, Tm2O3 0.75%, Eu2O3 0.5%, and ground in an agate mortar for 3 hours to obtain a uniformly mixed powder, which was then transferred to a high-purity corundum crucible;
[0063] (2) placing the powder obtained in step (1) in a muffle furnace at a temperature of 1300° C. and calcining for 2 hours, and after melting, quickly pouring the melt in the high-purity corundum crucible into deionized water for quenching to obtain a precursor glass, and then transferring it to an oven for drying to obtain a solid glass;
[0064] (3) grinding the solid glass obtained in step (2) in an agate mortar for 3 hours to obtain glass powder;
[0065] (4) Weigh 0.15 g of the powder obtained in step (3) and pour it into a mold with a diameter of 10 mm. Press it into a round green tablet using a hydraulic press with a holding pressure of 20 MPa for 60 seconds.
[0066] (5) The green disc obtained in step (4) is placed in a muffle furnace for heat treatment at 600° C. for 2 hours, and then cooled naturally to room temperature to obtain rare earth Dy 3+ / Tm 3+ / Eu 3+ Co-doped BaZn2(PO4)2 fluorescent glass-ceramic materials.
[0067] The XRD of the BaZn2(PO4)2 glass ceramic obtained in step (5) is shown in Figure 1. Both the crystalline peak and the amorphous peak exist, and the peak position and intensity of the crystalline peak correspond to the PDF card of BaZn2(PO4)2, indicating the existence of the corresponding crystalline phase. Under the excitation of 362nm light source, the measured emission spectrum is shown in Figure 5, showing that Dy 3+ / Tm 3+ / Eu 3+ The characteristic emission peak position of co-doped BaZn2(PO4)2 phosphate glass ceramics. The color coordinates are (0.3112, 0.3196), see Figure 8 The position indicated by "c" has a color temperature of 6667K, which is cold white light emission. The XRD spectrum of the fluorescent glass ceramic is shown in Figure 1(a), the model of the BaZn2(PO4)2 nanocrystal generated in the fluorescent glass ceramic is shown in Figure 1(b), the excitation spectrum of the glass ceramic is shown in Figure 3(a), the emission spectrum of the glass ceramic is shown in Figure 3(b), the emission spectrum of the glass ceramic is shown in Figure 5(a), the emission spectrum intensity change of the glass ceramic is shown in Figure 5(b), the fluorescence attenuation of the glass ceramic at 455nm under 362nm wavelength excitation is shown in Figure 6(a), the fluorescence attenuation of the glass ceramic at 575nm under 362nm wavelength excitation is shown in Figure 6(b), the Dy 3+ / Tm 3+ / Eu 3+ The energy level diagram is as follows Figure 7 As shown in the CIE chromaticity diagram of medium fluorescent glass ceramics Figure 8 shown.
[0068] Embodiment 3:
[0069] (1) BaCO3, ZnO, NH4H2PO4, H3BO3, Dy2O3, Tm2O3 and Eu2O3 were weighed according to the raw material ratio, and the raw materials were weighed according to the mass percentage: P2O5 32%, BaO 8%, ZnO 44%, B2O3 16%, Dy2O3 0.5%, Tm2O3 1.0%, Eu2O3 0.75%, and ground in an agate mortar for 4 hours to obtain a uniformly mixed powder, which was then transferred to a high-purity corundum crucible;
[0070] (2) placing the powder obtained in step (1) in a muffle furnace at a temperature of 1350° C. and calcining for 4 hours, and after melting, quickly pouring the melt in the high-purity corundum crucible into deionized water for quenching to obtain a precursor glass, and then transferring it to an oven for drying to obtain a solid glass;
[0071] (3) grinding the solid glass obtained in step (2) in an agate mortar for 4 hours to obtain glass powder;
[0072] (4) Weigh 0.2 g of the powder obtained in step (3) and pour it into a mold with a diameter of 20 mm. Press it into a green round tablet using a hydraulic press with a holding pressure of 40 MPa for 90 seconds.
[0073] (5) The green disc obtained in step (4) is placed in a muffle furnace for heat treatment at 650° C. for 4 hours, and then cooled naturally to room temperature to obtain rare earth Dy 3+ / Tm 3+ / Eu 3+ Co-doped BaZn2(PO4)2 fluorescent glass-ceramic materials.
[0074] The XRD of the BaZn2(PO4)2 glass ceramic obtained in step (5) is shown in Figure 1. Both the crystalline peak and the amorphous peak exist, and the peak position and intensity of the crystalline peak correspond to the PDF card of BaZn2(PO4)2, indicating the existence of the corresponding crystalline phase. Under the excitation of 362nm light source, the measured emission spectrum is shown in Figure 5, showing that Dy 3+ / Tm 3+ / Eu 3+ The characteristic emission peak position of co-doped BaZn2(PO4)2 phosphate glass ceramics. The color coordinates are (0.3192, 0.3189), see Figure 8The position indicated by "d" has a color temperature of 6209K, which is cold white light emission. The XRD spectrum of the fluorescent glass ceramic is shown in Figure 1(a), the model of the BaZn2(PO4)2 nanocrystal generated in the fluorescent glass ceramic is shown in Figure 1(b), the excitation spectrum of the glass ceramic is shown in Figure 3(a), the emission spectrum of the glass ceramic is shown in Figure 3(b), the emission spectrum of the glass ceramic is shown in Figure 5(a), the emission spectrum intensity change of the glass ceramic is shown in Figure 5(b), the fluorescence attenuation of the glass ceramic at 455nm under 362nm wavelength excitation is shown in Figure 6(a), the fluorescence attenuation of the glass ceramic at 575nm under 362nm wavelength excitation is shown in Figure 6(b), the Dy 3+ / Tm 3+ / Eu 3+ The energy level diagram is as follows Figure 7 As shown in the CIE chromaticity diagram of medium fluorescent glass ceramics Figure 8 shown.
[0075] Embodiment 4:
[0076] (1) BaCO3, ZnO, NH4H2PO4, H3BO3, Dy2O3, Tm2O3 and Eu2O3 were weighed according to the raw material ratio, and the raw materials were weighed according to the mass percentage: P2O5 28%, BaO 6%, ZnO 48%, B2O3 18%, Dy2O3 0.25%, Tm2O3 0.25%, Eu2O3 1.0%, and ground in an agate mortar for 3.5 hours to obtain a uniformly mixed powder, which was then transferred to a high-purity corundum crucible;
[0077] (2) placing the powder obtained in step (1) in a muffle furnace at a temperature of 1300° C. and calcining for 4 hours, and after melting, quickly pouring the melt in the high-purity corundum crucible into deionized water for quenching to obtain a precursor glass, and then transferring it to an oven for drying to obtain a solid glass;
[0078] (3) grinding the solid glass obtained in step (2) in an agate mortar for 3.5 hours to obtain glass powder;
[0079] (4) Weigh 0.15 g of the powder obtained in step (3) and pour it into a mold with a diameter of 10 mm. Press it into a green round tablet using a hydraulic press with a holding pressure of 20 MPa for 90 seconds.
[0080] (5) The green disc obtained in step (4) is placed in a muffle furnace for heat treatment at 600° C. for 4 hours, and then cooled naturally to room temperature to obtain rare earth Dy 3+ / Tm 3+ / Eu 3+ Co-doped BaZn2(PO4)2 fluorescent glass-ceramic materials.
[0081] The XRD of the BaZn2(PO4)2 glass ceramic obtained in step (5) is shown in Figure 1. Both the crystalline peak and the amorphous peak exist, and the peak position and intensity of the crystalline peak correspond to the PDF card of BaZn2(PO4)2, indicating the existence of the corresponding crystalline phase. Under the excitation of 362nm light source, the measured emission spectrum is shown in Figure 5, showing that Dy 3+ / Tm 3+ / Eu 3+ The characteristic emission peak position of co-doped BaZn2(PO4)2 phosphate glass ceramics. The color coordinates are (0.3264, 0.3240), see Figure 8 The position indicated by "e" has a color temperature of 5802K, which is near-white light emission. The XRD spectrum of the fluorescent glass ceramic is shown in Figure 1(a), the BaZn2(PO4)2 nanocrystal model generated in the fluorescent glass ceramic is shown in Figure 1(b), the surface SEM image of the fluorescent glass ceramic is shown in Figure 2(a), the EDS element mapping image of all elements of the fluorescent glass ceramic is shown in Figure 2(b-1), the EDS element mapping image of the Ba element of the fluorescent glass ceramic is shown in Figure 2(b-2), the EDS element mapping image of the Zn element of the fluorescent glass ceramic is shown in Figure 2(b-3), the EDS element mapping image of the O element of the fluorescent glass ceramic is shown in Figure 2(b-4), the EDS element mapping image of the P element of the fluorescent glass ceramic is shown in Figure 2(b-5), the EDS element mapping image of the Dy element of the fluorescent glass ceramic is shown in Figure 2(b-6), and the EDS element mapping image of the Tm element of the fluorescent glass ceramic is shown in Figure 2(b-7). The EDS element mapping image is shown in Figure 2(b-7), the EDS element mapping image of the Eu element of the fluorescent glass ceramic is shown in Figure 2(b-8), the TEM image of the fluorescent glass ceramic (showing the formation and size of the crystal) is shown in Figure 2(c), and the TEM image of the fluorescent glass ceramic (showing the existence and spacing of the lattice fringes) is shown in Figure 2(d). The excitation spectrum of the glass ceramic is shown in Figure 3(a), the emission spectrum of the glass ceramic is shown in Figure 3(b), the emission spectrum of the glass ceramic is shown in Figure 5(a), and the emission spectrum intensity change of the glass ceramic is shown in Figure 5(b). The fluorescence attenuation of the glass ceramic at 455nm under 362nm wavelength excitation is shown in Figure 6(a), and the fluorescence attenuation of the glass ceramic at 575nm under 362nm wavelength excitation is shown in Figure 6(b). The Dy 3+ / Tm 3+ / Eu 3+ The energy level diagram is as follows Figure 7 As shown in the CIE chromaticity diagram of medium fluorescent glass ceramics Figure 8 The temperature-dependent emission spectrum of the fluorescent glass ceramics (the inset is the normalized emission spectrum intensity of the sample at 298K-473K) is shown in Figure 9(a). The fluorescent glass ceramics ln[(I0 / It The relationship between )-1] and 1 / kT is shown in Figure 9(b).
[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that any modification or equivalent replacement of the technical solutions of the present invention does not depart from the spirit and scope of the technical solutions of the present invention and should be included in the scope of the claims of the present invention.
Claims
1. A phosphate fluorescent glass ceramic emitting positive white light, characterized in that: The phosphate fluorescent glass ceramic comprises, by mass percentage, 28-38% of P2O5, 6-12% of BaO, 36-48% of ZnO, and 14-18% of B2O3. The glass matrix is doped with Dy 3+ 、Tm 3+ and Eu 3+ , wherein the doped dysprosium-containing compound, thulium-containing compound and europium-containing compound account for 0.25%-1%, 0.25%-1% and x of the total mass of other raw materials respectively, 0.25%≤x≤1.0%.
2. The phosphate fluorescent glass ceramic according to claim 1, characterized in that: The dysprosium-containing compound is Dy2O3, the thulium-containing compound is Tm2O3, and the europium-containing compound is Eu2O3.
3. The phosphate fluorescent glass ceramic according to claim 1 or 2, characterized in that: The chromaticity coordinates of the phosphate fluorescent glass ceramic are (0.2951-0.5856, 0.3092-0.4136).
4. A method for preparing the phosphate fluorescent glass ceramic emitting positive white light according to any one of claims 1 to 3, comprising the following steps: 1) Raw material preparation: weigh the raw materials and mix them evenly to obtain a mixed powder; 2) Melting and quenching: The powder obtained in step 1) is calcined, and after melting, the melt is quenched to obtain a precursor glass, and the precursor glass is ground to obtain a glass powder; 3) Tableting: pouring the glass powder obtained in step 2) into a mold and pressing it into a round green tablet; 4) Heat treatment: The green disc obtained in step 3) is heat treated and cooled to room temperature to obtain rare earth Dy 3+ / Tm 3+ / Eu 3+ Co-doped BaZn2(PO4)2 fluorescent glass-ceramics.
5. The preparation method according to claim 4, characterized in that: In the step 2), the calcination temperature is 1300-1350° C. and the calcination time is 2-4 hours; The melt was poured into deionized water for quenching.
6. The preparation method according to claim 4, characterized in that: In step 3), a hydraulic press is used for pressing, and the hydraulic press uses a pressure of 20-40 MPa and a holding time of 60-90 seconds.
7. The preparation method according to claim 4, characterized in that: In the step 4), the heat treatment temperature is 600° C.-650° C., and the heat treatment time is 2-4 hours.